Determining the Gun shot Entry and-Exit wound on Skulls by using Post-mortem Computed Tomography Techniques - Rehman, Hidayat Ur (International Journal of Pathology, 2020)
Introduction: The identification of entry and exit hole on skull is not easy it needs precise and detailed examination. It depends upon the expertise of a forensic expert performing postmortem (autopsy) examination. The wound is usually determined by examining the characteristic features of entry and exit whole. The wound is usually measured by simple ruler by placing it next to the entry or exit wound after shaving the head. Post-mortem computed tomography technique develops a virtual 3Dimentional image of the skull. Hence in this study the entry and exit holes characteristics were easily differentiated. A digital autopsy 3D imagining technique used to differentiate between Entry and Exit wound on the skull without opening the skull and the results are accurate.Objective: To differentiate between entry and exit wholes on skull by using advance 3D imaging technique.Methods: A study was conducted in Forensic Medicine Department of Khyber Medical College Peshawar. 13 confirmed cases of gunshot wound in head were examined. In this study we used a Post-mortem computed tomography (PMCT) technique to make a three-dimensional image of the skull. As a result of this advance technique, examination of the skull has been improved with accuracy. The study design was a case control study that follows a group of victims who have a similar diagnosis i.e. gunshot injuries on head who underwent autopsy over a period of six months.Results: The diameter of entry hole due to gun shot in skull is smaller than the exit hole, beveling of inner and outer table is also helpful in identification of entry and exit hole.Conclusion: Post-mortem computed tomography (PMCT) technique develops a virtual 3Dimentional image of the skull which can help to give accurate dimensions of the wound. Furthermore, this technique can be used for digital autopsy conduction without opening of the body cavities. However, it is expensive and need specialized training.